Effect of valve design and anticoagulation strategy on 30‐day clinical outcomes in transcatheter aortic valve replacement: Results from the BRAVO 3 randomized trial. Issue 6 (19th July 2017) - Linke, Axel; Chandrasekhar, Jaya; Sartori, Samantha; Lefevre, Thierry; van Belle, Eric; Schaefer, Ulrich; Tchetche, Didier; Sardella, Gennaro; Webb, John; Colombo, Antonio; Windecker, Stephan; Vogel, Birgit; et al.
Abstract: Background: Selection of valve type and procedural anticoagulant may impact bleeding and vascular complications in transfemoral transcatheter aortic valve replacement (TAVR). We sought to compare outcomes by valve [balloon expandable (BE) or non‐BE] and anticoagulant [bivalirudin vs. unfractionated heparin (UFH)] type from the BRAVO‐3 trial. Methods: BRAVO‐3 was a randomized multicenter trial including 500 BE‐TAVR and 282 non‐BE TAVR patients, randomized to bivalirudin versus UFH. Selection of valve type was at the discretion of the operator but randomization was stratified according to valve type. Total follow up was to 30 days. We examined the incidence of Bleeding Academic Research Consortium type ≥3b bleeding, major vascular complications and all ischemic outcomes at 30‐days. Outcomes were adjusted using logistic regression analysis. Results: Of the trial cohort, 63.9% were treated with BE valves ( n  = 251 bivalirudin vs. n  = 249 UFH) and 36.1% with non‐BE valves ( n  = 140 bivalirudin vs. n  = 142 UFH). Patients treated with non‐BE valves were older, with higher euroSCORE I. At 30 days, there were nonsignificant differences between the two valve types for adjusted risk of all‐cause death (HR 2.07, 95% CI 0.91–4.70, P  = 0.084) and major vascular complications (HR 1.78, 95% CI 0.97–3.26, P  = 0.062) with non‐BE compared with BE valves, but all other outcomes were similar. A significant interaction was observed between valve and anticoagulant type, with lower risk of major vascular complications with bivalirudin compared with UFH in non‐BE TAVR ( P ‐interaction = 0.039). Conclusions: Majority of patients in the BRAVO 3 trial received BE valves. At 30‐days, adjusted risk of clinical outcomes was similar with non‐BE vs. BE valves. A significant interaction was observed between valve type and procedural anticoagulant for lower risk of major vascular complications with bivalirudin versus UFH in non‐BE TAVR.